The Assessment of the Antibacterial Activity of some Plant Extracts on Normal and Pathogenic Microflora from Milk - Claudia Paşca; Liviu Al. Mărghitaș; Dan Dezmirean; Otilia Bobiș; Victorița Bonta; Rodica Mărgăoan; Flore Chirilă; Nicodim Fit (Scientific Papers Animal Science and Biotechnologies, 2023)
This paper presents the evaluation of antibacterial activity of some plant alcoholic extracts over bacteria in milk as an alternative to current antibiotics. Tests were conducted on alcoholic extracts from sage (Salvia officinalis), two hop species Brewers Gold and Perle and two essential oils (rosemary - Rosmarinus officinalis and lavender - Lavandula angustifolia). The antibacterial susceptibility has been evaluated over 24 strains isolated from normal milk and mastitis milk, belonging to Staphylococcus, Vibrio, Serratia, Aeromonas and Bacillus genera. The obtained results show the best antibacterial effect with rosemary essential oil, having areas of inhibition as big as 28 mm, with an average of 16.4 mm. Weaker antimicrobial effect was obtained with alcoholic extract of sage where the average of inhibition diameters were 12.2 mm. Bacterial species isolated from mastitis were more sensitive to treatment with plant extracts compared with species isolated from normal milk. Among the tested bacteria, the strains from Staphylococcus type had the highest sensitivity, while Vibrio strains were more resistant. The results obtained open the prospect of using these herbal extracts as an alternative to the use of antibiotics in the treatment of mastitis and also aim at getting safer products from a microbiological point of view, with less antibiotic residues in milk.